Self‐Assembly of a Giant Molecular Solomon Link from 30 Subcomponents1. Issue 42 (28th August 2014) - Schouwey, Clément; Holstein, Julian J.; Scopelliti, Rosario; Zhurov, Konstantin O.; Nagornov, Konstantin O.; Tsybin, Yury O.; Smart, Oliver S.; Bricogne, Gérard; Severin, Kay
Abstract The synthesis of topologically complex structures, such as links and knots, is one of the current challenges in supramolecular chemistry. The so‐called Solomon link consists of two doubly interlocked rings. Despite being a rather simple link from a topological point of view, only few molecular versions of this link have been described so far. Here, we report the quantitative synthesis of a giant molecular Solomon link from 30 subcomponents. The highly charged structure is formed by assembly of 12 cis‐blocked Pt2+ complexes, six Cu+ ions, and 12 rigid N‐donor ligands. Each of the two interlocked rings is composed of six repeating Pt(ligand) units, while the six Cu+ ions connect the two rings. With a molecular weight of nearly 12 kDa and a diameter of 44.2 Å, this complex is the largest non‐DNA‐based Solomon link described so far. Furthermore, it represents a molecular version of a "stick link".